Coaching efficacy among Malaysian SUKMA 2012 coaches / Raja Nurul Jannat Raja Hussain - Raja Hussain, Raja Nurul Jannat (2013)
Coaches have the responsibility in guiding the athletes to be successful in their sports performance by helping in improving their skills. One of the factors that may influence athletes to be able to perform at their optimal level is through their beliefs in their coaches carrying out the duties to coach. The purpose of this study was to determine the differences among Malaysian SUKMA 2012 coaches with regard to their playing experience, coaching experience, and coaching courses attended with coaching efficacy. A total of 323 coaches who coached in Sukan Malaysia (SUKMA 2012) which were selected through purposive sampling participated in this study. Coaching Efficacy Scale (CES) questionnaire was used to measure the coaches coaching efficacy. Results showrd that the coaches’ level of coaching efficacy was high for all subscales namely character building (M= 7.97, SD = .64), motivation (M = 7.91, SD = .58), technique (M= 7.91, SD = .64), and game strategy (M= 7.84, SD = .60). There was a significant difference for coaches’ level of playing experience (p<.05) in motivation and character building efficacy. Coaching experience also showed significant difference (/K.05) in all subscales of coaching efficacy. Level of coaching courses attended (p<.05) did showed significant difference, however, only in motivation subscale. Furthermore, multiple regression showed there was a significant relationship {F (6, 316) = 14.76,/K0.001} in both level of coaching courses attended and level of playing experience that coaches have with the overall coaching efficacy. In conclusion, coaches who have both playing experience and attend to coaching course helped in enhancing their level of coaching efficacy.